IPC Oxford Private Equity Research Symposium. Issue 3 (22nd November 2021) - Brown, Gregory; Jenkinson, Tim; Harris, Robert S.; Bukovec, Petra; Ivashina, Victoria; Strömberg, Per Johan; Kinniry, Fran; Rogers, Alex
Abstract : One of the world's foremost authorities on global private equity offers four predictions: #1: The net returns to LPs from private equity buyouts will likely continue to outperform public equity market returns both in the U.S. and abroad, causing investors' global allocations to PE buyouts to keep increasing. #2: European VC funds will continue to attract much more capital, partly because many institutional investors have little invested in VC, having abandoned it after the dot‐com bubble. But whether the recent flood of capital into VC—in both the U.S. and Europe—can be profitably deployed is unclear, given the possible consequences of too much money chasing too few innovations. #3: Private equity for retail public investors will grow, but likely more slowly than many think. The current fund‐of‐funds models promise wide portfolio diversification along with co‐investment and secondary opportunities, and with a much more investor friendly fee structure. #4: Special Purpose Acquisition Companies, or SPACS, will become mainstream despite involving more risk than commonly supposed. Although many investors will sustain major losses, and the watchword is "Buyer Beware"—there is no banker certification of such deals—the structure of SPACS is defensible, and the transactions offer opportunities for the vigilant. The speakers offer a number of reasons why PE's outperformance of public markets is likely to shrink. One is the failure of return comparisons to adjust net returns for the risk and illiquidity of PE investments. Another is the possibility that a 40‐year decline in interest rates could be followed by rising rates. With very low interest rates effectively making liquidity "almost free, " investors demand little compensation for investing in illiquid assets. If and when interest rates begin rising, liquidity will become more expensive, and allocations to private equity and PE valuations will fall. Nevertheless, buyouts and venture capital will continue to play an important part in the portfolios of large institutions. Whereas virtually all LPs used to view their PE investments as "buy and hold" investments, the expansion of the secondary market is now providing many with ways to exit their portfolios, or even individual assets, at interim stages. And the PE practitioners on this panel noted that secondary markets are expected to experience rapid growth, particularly for functions such as asset‐liability management. Vanguard's Fran Kinniry stressed the importance of manager selection in private capital, noting that although the "persistence" of GP outperformance has fallen, the performance gap between the top PE firms and the bottom quartiles is still "dramatically wider" than the gap between the top and bottom quartiles of active public market managers. And both Kinniry and Rogers described the U.S. market as still "nowhere near saturation, " when considering the entire range of PE activity. Indeed, both envision an ongoing process in which successful public companies end up spinning off smaller units into private companies that eventually become public themselves. In this fashion, private equity is seen as complementing public equity portfolios—and the demand for PE investments ends up encouraging more supply.